Sustainable Growth and Fair Competition: The Dark Side of the Digital Revolution (UNWE Yearbook, 2024)
Digitalization has led to a “revolution” over the last few decades: physical distances have been deleted; access to information and services has become easier; communications have become immediate and cost-efficient. Who cannot enjoy the results of the “digital revolution”? Is the use of digital tools a right “per se” or solely where necessary to exercise other rights? Digitalization can simplify life of persons, economic activities and public administration, but it costs and could be an obstacle for people not ready to use it. One way to facilitate the diffusion of digital tools is to invest State resources in infrastructures, but harmful tax competition among States has a distortive effect in terms of fair distribution of revenue and of availability of funds to address the digital progress. The aim of the present work is to foster the analysis of the implications of digital transformation and its links with the distribution of tax rights and the availability of funds. It is crucial for jurisdictions not to lose the momentum and boosting their digital transformation to make themselves competitive, for that it is necessary to reach international agreements on collecting revenue from digital economy, making tax competition between States fairer.